LAW ENFORCEMENT AGAINST NARCOTICS ABUSE FROM THE PERSPECTIVE OF CRIMINAL LAW IN INDONESIA - Khairul Umam; Moh Syahrul Alim; Wahyudi Efendy; Seftiawan Firmansyah; Susilo Bambang Yudhoyono (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
Drug abuse is an extraordinary crime because its impacts not only threaten individual health but also damage the social fabric and the nation's future generations. Law No. 35 of 2009 concerning Narcotics serves as a form of legal protection and a repressive measure by the state to combat drug abuse and illicit trafficking. However, in practice, law enforcement still finds disparities between users, dealers, and dealers. Many users who should receive rehabilitation are instead sentenced to prison, while dealers receive reduced sentences. This study aims to examine the effectiveness of law enforcement against drug abuse in Indonesia, the inhibiting factors, and solutions that can be implemented to achieve substantive justice. This study uses a normative juridical method with a statutory and conceptual approach. The results indicate that law implementation has not been effective due to weak coordination between law enforcement agencies and low public legal awareness.